Nutrient recovery in cultured meat systems: Impacts on cost and sustainability metrics - Myers, Gabrielle M.; Jaros, Kate A.; Andersen, Daniel S.; Raman, D. Raj (Frontiers in Nutrition, 2023)
A growing global meat demand requires a decrease in the environmental impacts of meat production. Cultured meat (CM) can potentially address multiple challenges facing animal agriculture, including those related to animal welfare and environmental impacts, but existing cost analyses suggest it is hard for CM to match the relatively low costs of conventionally produced meat. This study contextualizes CM’s protein and calorie use efficiencies, comparing CM to animal meat products’ feed conversion ratios, areal productivities, and nitrogen management. CM appears to have greater protein and energy areal productivities than conventional meat products. Recovering portions of waste nitrogen from spent CM media will be required for CM to surpass the nitrogen use efficiency of meat produced in swine and broiler land-applied manure systems. The CM nutrient management costs, arising from wastewater treatment and land application, are estimated to be more expensive than in conventional meat production.